Gestión financiera de la Empresa “Ruforcorp S. A.”, en la parroquia Pimocha del cantón Babahoyo, periodo 2019-2020. - Rodríguez Valero, Solange Thais (2022)
The Covid - 19 pandemic has generated serious connotations in the health and economic field; since at the beginning of the sanitary emergency there were restrictions of mobility and social relations, which generated that the business sector of Ecuador was affected; many companies closed their businesses due to the low level of sales, on the other hand, other organizations adapted to the new scenario. Given the influence that the health crisis has generated in the national economy, the research objective was to analyze the influence of the Covid-19 pandemic on the financial situation of the company Ruforcorp S.A. The methodology applied in this case study is based on a quantitative approach, while the types of research were descriptive and documentary, and the method used was inductive. The techniques considered were direct observation of the company's financial statements and an interview with the Ruforcorp S.A. manager of the branch located in Rcto. Cañales de la Parroquia San Juan. The results of the study show that the Covid-19 pandemic did not affect the financial situation of the company under study; that is, there was an efficient management of financial risks that prevented financial problems. The conclusions of the investigation are that the financial situation of Ruforcorp S.A. is at acceptable levels.